Recent Developments to the ANSWERS® Monte Carlo Codes MONK® and MCBEND® - Fildes Jessica; Richards Simon; Bird Adam; Cox Andrew; Fry Timothy; Hanlon David; Jones Brian; Long David; Tantillo Francesco; Wright George; Hiles Richard (EPJ Nuclear Sciences & Technologies)
MONK® and MCBEND® are two advanced Monte Carlo codes developed by the ANSWERS® Software Service, which have been used in over 30 countries worldwide for a range of applications, and have been well-established in the UK criticality and shielding communities respectively over the course of several decades. These codes continue to be actively developed to meet the needs of their users. We introduce a number of new developments which have been implemented in recent releases of these codes, or will be implemented in the next release. As MONK and MCBEND share a significant amount of source code, some of these new developments are in common between the two codes and some are specific to each. Improvements to the physics include stochastic mixing of bound thermal scattering data, Doppler broadening rejection correction, improved support for low temperature analyses in MONK, and modelling of photonuclear reactions in MCBEND. A novel approach for transferring irradiated geometry components between models has been developed for burn-up credit applications in MONK. A list mode facility has been added for subcritical analyses, including a model for the full distribution of neutron multiplicity. The geometry capabilities have been enhanced by the addition of novel stochastic geometry algorithms for modelling highly disordered heterogeneous mixtures and random distributions of shapes. IGES-formatted CAD geometries may be imported into MONK and MCBEND and approximated as a set of triangular surface polygons in a new Fractal Geometry body. The new IGES import feature additionally offers dedicated particle tracking routines that process the model geometry within the IGES file exactly, allowing the geometry to be used in MONK and MCBEND with no approximation. New estimators of the adjoint flux in both codes and adjoint-weighted kinetics parameters in MONK have been implemented, in addition to a pulse height distribution detector resolution model in MCBEND. A brief discussion of parallel processing in both codes is presented. New developments to the tools available in the accompanying Visual Workshop integrated development environment are also described.